Government Net Contribution and Foreign Balance as Offset to Savings - Neisser, Hans (The Review of Economics and Statistics, 1944)
T HE publication of Keynes' General Theory in I936 not only ushered in a new era of theoretical thinking in economics, but also proved a stimulus to statistical work of both explanatory and prognostic nature. When it was noticed that aggregate savings retrospectively always must be equal to aggregate investment (despite investment decisions and saving decisions being mutually independent), the idea arose to use investment series for forecasting aggregate income and employment, provided that aggregate saving as a function of income should prove sufficiently stable over time. The first preparatory step in this direction was an analysis of how the current saving propensities were allowed to materialize into actual savings by offsetting investment activities, which thus assisted in maintaining an aggregate income just large enough to generate the actual amount of saving in question. When such analysis was undertaken for the United States, it was at once realized that, besides private investmenkt, other forces were operating to the ssaving propensity of the community. The offset series, prepared in the Division of Research and Statistics of the Board of Governors of the Federal Reserve System, about which the public was informed by Dr. L. Currie's testimony before the T. N. E. C.1 contained, in addition to three private investment series (i) plant and equipment, (2) private housing expenditure, (3) net change inventories three other offsets, which we may briefly call (4) government net contribution, (5) net foreign balance (on current account), (6) net change in consumers' credit. The introduction of number (5) is necessary because the basic identity